Multi-chronometer thermochronological modelling of the Late Neoproterozoic to recent t-T-evolution of the SE coastal region of Brazil - Krob, Florian; Glasmacher, Ulrich A. (Journal of South American earth sciences, 2019)
South-eastern Brazil is as an important geological archive for understanding and reconstructing various plate tectonic stages of the Wilson Cycle. In the Neoproterozoic, the area of the today's South Atlantic passive continental margin (SAPCM: e.g. between São Paulo and Laguna) of south-eastern Brazil underwent subduction, followed by the collision of the contemporary plates of South America and Africa creating a Neoproterozoic orogeny within the supercontinent Gondwana. During the Palaeozoic and Lower Mesozoic (stage 1), the future SAPCM, as an intracratonic area, experienced erosion, denudation of the Neoproterozoic mobile belts (Pan African/Brasiliano orogeny), and large basin formation (Paraná Basin) (stage 2). Possibly plume-driven pre-to syn-rift (embryonic), ocean spreading (juvenile), and post-break up (mature) processes led to the recent evolution of the SAPCM since the Upper Mesozoic (stage 3). For the first time, this research aims to reconstruct the syn-to post-orogenic t-T-evolution of Neoproterozoic basement rocks of the SE coastal region of Brazil covering the entire geological evolution since the Late Neoproterozoic. Therefore, this study uses geochronological and thermochronological data combined with numerical modelling. This includes published geochronological data of Neoproterozoic basement samples such as U-Pb, Sm-Nd and Rb-Sr analyses, and low temperature thermochronology (LTT) data revealed by K/Ar, 40Ar/39Ar analyses. To this existing LTT data set, we report new apatite (AFT) and zircon (ZFT) fission-track, and (U-Th-Sm)/He (AHe, ZHe) data. Numerical modelling of that LTT data attached to the existing geochronological data indicates the following evolution: - Stage 1: In the central part of the future SAPCM, the Pan African/Brasiliano post-orogenic cooling and exhumation (uplift and erosion of Neoproterozoic rocks to the surface) history occurs in three phases: (i) rapid Late Neoproterozoic exhumation, (ii) a period of relative thermal stability (temperatures of about 200-300°C) in which rocks reside at upper crust levels during the Early Cambrian to Devonian, and (iii) a second rapid exhumation phase moving the Neoproterozoic basement rocks to the surface during the Devonian. The northern and southern parts indicate a distinct post-orogenic exhumation suggesting faster cooling and exhumation from the Late Neoproterozoic to Devonian/Carboniferous than in the central section. - Stage 2: A phase of subsidence leading to the formation of the Paraná Basin followed by pre-to syn-rift processes and the emplacement of the Paraná-Etendeka flood basalts. - Stage 3: Post-South Atlantic break up processes, such as erosion and exhumation.
Gesehen am 28.08.2019